A Certification Framework for Virtual Reality and Metaverse Training Scenarios in the Maritime and Shipping Industry - Markopoulos Evangelos; Nordholm Aksel David; Illiade Stavroula; Markopoulos Panagiotis; Faraclas John; Luimula Mika (United States, 2022)
The Covid-19 pandemic enable advanced technologies to find areas of application that significantly eliminate physical presence. This paper presents an analysis of the maritime and shipping VR and Metaverse training certification demand, the requirements that need to be fulfilled for VR training scenarios to be certified, and the overall certification process that can be followed. The research is based on primary and secondary research with an extensive academic literature review, a survey with 80 maritime participants, three interviews with industry experts in maritime VR training and certification, case studies on the maturity and the readiness on the VR training in maritime and shipping, and the presentation of the latest virtual training certification standards from a leading maritime classification organization. The research results indicate an initial VR training certification process that can be used as a guide for VR training organizations on their efforts to certify their professional training applications and technologies.
Creativity, Innovation and Entrepreneurship: Proceedings of the 13th AHFE International Conference on Creativity, Innovation and Entrepreneurship, New York, USA July 24-28, 2022